TRIPS flexibilities on patent enforcement: Lessons from some developed countries relating to pharmaceutical patent protection - Joshua D. Sarnoff (South Centre, 2020)
Authority for national judiciaries to issue permanent and preliminary injunctions is required by the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), Articles 44 and 50. But the TRIPS Agreement does not require the issuance of injunctions in any particular circumstances, and does not harmonize the laws on which national jurisdictions derive their injunctive relief authorities. Thus, countries remain free to refuse prohibitory injunctive relief for adjudicated or likely patent infringement, particularly if “reasonable compensation” is offered in the form of an “ongoing royalty” or an “interim royalty” payment, which acts similarly to a compulsory license. This paper explains the existing legal standards for permanent and preliminary injunctions in the United States and Canada and discusses trends regarding the issuance or denial of injunctions for pharmaceutical patents in those jurisdictions (with occasional reference to other common-law jurisdictions). Although judges in these jurisdictions more routinely deny preliminary prohibitory injunctions, legislation linking generic pharmaceutical regulatory approvals to the patent system and imposing stays of such approvals normally avoid the need for such preliminary injunctions. Consistent with the TRIPS Agreement, developing country judges may make different choices, based on the ability to provide reasonable compensation for harms or based on a different weighing of the importance of assuring affordable access to medicines relative to providing innovation incentives.
Keywords: 300; Access to Medicines; Affordable Medicines; Canada; Compulsory Licenses; COVID-19; Flexibilities; Generic Medicines; Health; Injunction; Innovation; Intellectual Property; Pandemic; Patent; Patent Linkage; Permanent Injunction; Pharmaceuticals; Preliminary Injunction; Public Health; TRIPS; United States (US)